Assessment of simple reaction time in badminton players - Bankosz, Z.; Nawara, H.; Ociepa, M. (Trends in Sport Sciences, 2013)
Badminton is considered a sport requiring high levels of all constituent speeds. Few available instances of research in this area maintain that badminton players are characterised by high levels of movement speed, nervous conductivity and agility. Aim of the Study. This work was aimed to determine the times of simple reaction in male and female badminton players by assessing differences between badminton players and controls. Assessment of reaction times also involved a comparison of results obtained during the experiments with standards available in the literature. Material and Methods. Subjects were divided into four groups: two groups of top level junior players (10 boys and 6 girls); 26 non-playing boys and 6 non-playing girls. The measurements were conducted with the use of the MRK-80 reaction meter. Results. Arithmetic means, minimum and maximum values, standard deviation and coefficient of variation were calculated. Student`s t-test was conducted to compare the results in the groups. Conclusions. Badminton players display shorter reaction times than non-players, which is probably the consequence of practicing badminton. The difference was found between results of all tests taken by boys and most tests taken by girls. The comparison of the obtained reaction times displayed by badminton players with the available standards proved that their values were mostly average, which might be the consequence of the fact that in badminton, like in many other sports, more complex factors, e.g. choice reactions, anticipation, etc., are of far greater signifi cance.